Political discourse in online communities as a communication technology of network control - Podshibyakina, Tat’yana Aleksandrovna (Opción, 2019)
The paper is aimed at identifying the potential possibilities of the power in the management of the networking political discourse formation process via network, discursive and communication theoretical and methodological approaches. As a result, technological discursive possibilities of external influence on the closed online communities and their social effects were identified. In Conclusion, a promising direction of research is the further development of the topic in the direction of studying the problems of managing democratic processes, network activism, discursive communicative technologies of political manipulation and forms of resistance to their dissemination in the form of various anti-censorship technologies.